Relationship between Vaginal Sialidase Levels with Threatened of Preterm Labour - Bambang Sulistyo; Najoan N Warouw; Eddy Suparman (Indonesian Society of Obstetrics and Gynecology, 2018)
Objective: To investigate the association between vaginal sialidase levels and threatened of preterm labor. Methods: A cross sectional study design was used. Subjects were divided into two groups; the first group were pregnant women with threatened of preterm labour, whereas the second were preterm pregnant women in Prof. Dr. R.D. Kandou Manado hospitals and network hospitals, during the period between August 2016 and October 2016. Data were analyzed with SPSS version 20 to see the significancy levels. Results: From the 16 pregnant women with threatened of preterm labor and 16 pregnant women with preterm pregnant, the statistical t test showed that there were significant differences average level of sialidase vagina between the threatened of preterm labor and preterm pregnant group (p = 0.000). Conclusion: There is a relationship between the incidence threatened of preterm labor with vaginal sialidase levels. Keywords: bacteria, threat of preterm labour, vaginal sialidase